2018 12th International Symposium on Medical Information and Communication Technology (ISMICT) 2018
DOI: 10.1109/ismict.2018.8573694
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the Sternotomy Wires and Aortic Valve Implant on the On-Body UWB Radio Channels

Abstract: In this paper, the impact of the sternotomy wires and aortic valve implant on the ultra wideband (UWB) channel characteristics is studied. The evaluations are performed by calculations, measurement data analysis, and power flow simulations. The aim is to show that implants, which consist of steel, titanium, and other highly conductive materials, do have clear effect on the signal propagation even inside the tissues. This impact should be taken into account when using in-body or onbody communications devices, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2
1

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(25 citation statements)
references
References 10 publications
1
24
0
Order By: Relevance
“…The presented results showed that sternotomy wires have clear impact on the channel characteristics. This paper further extends the studies presented in [32] and [33] by including detailed calculations for different intra-body propagation path options, new experimental measurements, and simulations results. The main contribution is to verify propagation path calculations with the experimental data and with simulation results for two cases, for a subject that has sternotomy wires and an aortic valve implant and for a subject without any implants To our knowledge, this paper presents, for the first time, a comprehensive study on the impact of sternotomy wires and a medical implant on the channel characteristics by studying intra-body propagation in the vicinity of the on-body antennas.…”
Section: Introductionsupporting
confidence: 61%
See 4 more Smart Citations
“…The presented results showed that sternotomy wires have clear impact on the channel characteristics. This paper further extends the studies presented in [32] and [33] by including detailed calculations for different intra-body propagation path options, new experimental measurements, and simulations results. The main contribution is to verify propagation path calculations with the experimental data and with simulation results for two cases, for a subject that has sternotomy wires and an aortic valve implant and for a subject without any implants To our knowledge, this paper presents, for the first time, a comprehensive study on the impact of sternotomy wires and a medical implant on the channel characteristics by studying intra-body propagation in the vicinity of the on-body antennas.…”
Section: Introductionsupporting
confidence: 61%
“…Dielectric values for different human tissues can be found in [39]. When considering signal propagation in the asymmetric case, one option is to consider the most direct path from the Tx antenna towards the valve/wire and further towards the Rx antenna, as presented in [32]. Another option is to consider, which of the possible paths are the fastest for propagation, i.e.…”
Section: A Asymmetric Case With Antenna Distance 65 CMmentioning
confidence: 99%
See 3 more Smart Citations